2021
DOI: 10.28918/jaais.v2i1.4075
|View full text |Cite
|
Sign up to set email alerts
|

Kinerja Keuangan Bank Sebelum dan Sesudah Konversi ke Bank Syariah (Studi Pada Bank NTB Syariah)

Abstract: This study aims to determine how the impact of the conversion process of BankNTB Syariah which was previously a conventional bank on the financialperformance of Bank NTB Syariah, by comparing the financial performance beforeand after the conversion process is carried out. The approach used in this study isa descriptive qualitative method with financial statement analysis techniques toanswer research questions, by comparing the liquidity ratio (Loan to Deposit Ratio)and the profitability ratio (Return on Assets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The analysis results indicate that the bank achieved an efficiency level of only 93% for the financing output variable and 67% for the income output variable, based on the Projected Value. The decrease in efficiency value for Bank NTB Syariah after the conversion aligns with the findings of a study conducted by Fahdiansyah (2021). The research revealed an increase in the financial performance of PT.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The analysis results indicate that the bank achieved an efficiency level of only 93% for the financing output variable and 67% for the income output variable, based on the Projected Value. The decrease in efficiency value for Bank NTB Syariah after the conversion aligns with the findings of a study conducted by Fahdiansyah (2021). The research revealed an increase in the financial performance of PT.…”
Section: Resultssupporting
confidence: 86%
“…By doing so, it is hoped that Bank NTB Syariah can enhance its efficiency and achieve optimal performance in the future [22]. Source: The DEA assumes VRS, and the data will be processed in 2023…”
Section: Iciebdsmentioning
confidence: 99%
“…Pambuko and Pramesti (2020) report that the conversion of Bank of Aceh to a sharia commercial bank has led to improvements in the level of non-performing financing but a decline in profitability. On the other hand, Fahdiansyah (2021) found that the financial performance of Bank of NTB improved after its conversion to a sharia commercial bank, although further improvements are needed. According to Al Kautsar et al (2019), the stability of the bank after the conversion process is expected to be better than when it was a conventional commercial bank.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, it has resulted in a corresponding decrease in profitability. Bank of NTB's financial performance has improved since its transition to a full-fledged Islamic bank, but it has not yet reached its full potential (Fahdiansyah, 2021). This situation is attributable to the ongoing economic challenges faced by the people of NTB following the 2018 earthquake when the conversion occurred.…”
Section: Theoretical Frameworkmentioning
confidence: 99%